Who is God? : key moments of biblical revelation - Bauckham, Richard (Grand Rapids, Michigan : : Baker Academic, a division of Baker Publishing Group, 2020)
"An internationally respected scholar probes the deep meaning of some well-known moments in the biblical story in order to address the key question the Bible is designed to answer: Who is God?"--
Includes bibliographical references and index.
Keywords: God -- Biblical teaching